2006
DOI: 10.1177/000348940611501004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Flexible Laryngoscope with Calibrated Sizing Function to Intraoperative Measurements

Abstract: The calibrated endoscope is capable of providing useful sizing information for laryngeal structures, and these measures correspond quite well to more direct measurements in the operating room. Objective sizing of laryngeal lesions is complicated by subjective judgments of lesion boundaries, which can be indistinct in many cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…A study by Kobler et al in 2006 developed a prototype fiberoptic transnasal laryngeal endoscope with an additional optical system for calibration of images. However, they reported rather high margins of error for lesions with well-defined borders, ranging from 14 to 50% [27]. …”
Section: Discussionmentioning
confidence: 99%
“…A study by Kobler et al in 2006 developed a prototype fiberoptic transnasal laryngeal endoscope with an additional optical system for calibration of images. However, they reported rather high margins of error for lesions with well-defined borders, ranging from 14 to 50% [27]. …”
Section: Discussionmentioning
confidence: 99%
“…In 2006, Kobler et al (5) designed a device that could project 23 individual green standard spots into the field of view of the endoscope by installing a 150-mW green diode laser source within the nasopharyngeal endoscope, and by placing a glass plate printed a lattice scale between the optical fibers and the lens. As a nasopharyngeal endoscope, it can be used even during normal phonation.…”
Section: Discussionmentioning
confidence: 99%
“…These methods, while revolutionary, had limitations with respect to image distortion correction and were very labor intensive. Other work by Kobler et al [5] has demonstrated that individual measurements obtained via flexible bronchoscopic correlate well with endotracheal tube measures. In this study the possibility of automatic distortion correction and 3D rendering of 2D image sequences was examined and developed into a usable technique which was applied to a test case.…”
Section: Introductionmentioning
confidence: 86%
“…A qualitative point cloud model was then created by applying this analysis to each frame in the sequence. In order to achieve a quantitative model an instrument of a known dimension was placed in the airway and the video analyzed as above [5,7]. The known instrument measurements were then used to apply a scale to the rest of the model.…”
Section: Part Imentioning
confidence: 99%
See 1 more Smart Citation